2019
DOI: 10.1016/j.cyto.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Salivary levels of MPO, MMP-8 and TIMP-1 are associated with gingival inflammation response patterns during experimental gingivitis

Abstract: Aim: This study aimed to investigate the association between salivary levels of myeloperoxidase (MPO), neutrophil elastase (NE), soluble urokinase-type plasminogen activator receptor (suPAR), matrix metalloproteinase (MMP)-8 and tissue inhibitor of matrix metalloproteinases (TIMP)-1 and gingival inflammation development during an experimental gingivitis study. Methods: A three-week experimental gingivitis study was conducted. Clinical recordings of dental plaque biofilm (Modified Quigley Hein Plaque Index, TQH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…Nascimento's study also showed MMP-8 signi cantly increased during the process of experimental gingivitis [23], all these data indicated that MMP-8 increased with the development of gingival in ammation and kept stable in the subsequent stage of disease.…”
Section: Discussionmentioning
confidence: 81%
“…Nascimento's study also showed MMP-8 signi cantly increased during the process of experimental gingivitis [23], all these data indicated that MMP-8 increased with the development of gingival in ammation and kept stable in the subsequent stage of disease.…”
Section: Discussionmentioning
confidence: 81%
“…Further investigation by Nascimento et al . (37) measured the salivary levels of MMP‐8, myeloperoxidase, and TIMP‐1, and suggested that the faster responders had greater neutrophil involvement. A larger number of participants in future studies may help with identification of these kinds of groups, using the methods presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Commercially available ELISA kits were used to measure levels of TIMP‐1 (Biotrak ELISA systems, Amersham Biosciences UK Ltd, Buckinghamshire, UK), MPO (Immundiagnostik AG, Bensheim, Germany), and PMN elastase (Bender MedSystems mbH, Vienna, Austria) in saliva according to the manufacturer's guidelines as described before …”
Section: Methodsmentioning
confidence: 99%